The Effect of Education and Training on Employee Performance at PT Hadji Kalla Toyota Palopo - Ummah, Nur Ainun Mustiha; Sukri, Sukri; Riyanti, Riyanti (PT. EQUATOR SINAR AKADEMIA, 2025)
This study aims to analyze the effect of education and training on employee performance at PT Hadji Kalla Toyota Palopo. The research method used is quantitative with a population of 70 employees and a sample of 41 employees using random sampling techniques. Data were collected through observation and questionnaires, and analyzed using multiple linear regression analysis. The results showed that education did not show a significant effect on employee performance while training had a significant positive effect on employee performance. Simultaneously, education and training had a significant effect on employee performance. The implications of the results of this study emphasize the importance of training in improving employee performance, so that companies are advised to focus on effective training programs in human resource development.